Tainoe i iavnoe . Secret and Manifest - Karpov, Boris Leonidovich (CSDF, 1973)
"Goals and Actions of the Zionists". According to the film's narrative Zionosm is identical with imperialism. Film interprets Zionism as anti-Soviet international conspiracy. Manifest anti-semitic film.